2012
DOI: 10.1039/c1dt11629k
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of main group and late transition metal complexes using orthometallated imine ligands

Abstract: Several late transition metal and main group orthometallated imine complexes were synthesized by utilizing ortholithiated imine precursors. Magnesium, aluminum, zinc, copper(I), and tin(IV) complexes were isolated and characterized. Subsequent reactions with electrophiles such as Ph(2)PCl, MeI and I(2) yielded several functionalized products, including a new iminophosphine ligand and its corresponding copper(I) complex. The coordination modes of the orthometallated imine ligands, as well as the structures of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Additionally, both Zhu's and Sundholm's calculations reveal that lithium counterions play an important role in these organocopper complexes [74,75]. As shown in Scheme 11, the C,N-chelated dicopper compounds 37,38 and 40-42 documented in the literature are generally macrocyclic neutral species since the two negative ligand charges are exactly balanced with two Cu(I) atoms [76][77][78][79][80][81][82]. An early example of structurally well-defined alkylcopper compounds was [Me3SiCH2Cu]4, in which trimethylsilyl groups not only pose steric hindrance to increase the stability but also improve the solubility by virtue of the lipophilicity of the silicon groups [83,84].…”
Section: Binuclear Macrocyclic Copper Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, both Zhu's and Sundholm's calculations reveal that lithium counterions play an important role in these organocopper complexes [74,75]. As shown in Scheme 11, the C,N-chelated dicopper compounds 37,38 and 40-42 documented in the literature are generally macrocyclic neutral species since the two negative ligand charges are exactly balanced with two Cu(I) atoms [76][77][78][79][80][81][82]. An early example of structurally well-defined alkylcopper compounds was [Me3SiCH2Cu]4, in which trimethylsilyl groups not only pose steric hindrance to increase the stability but also improve the solubility by virtue of the lipophilicity of the silicon groups [83,84].…”
Section: Binuclear Macrocyclic Copper Complexesmentioning
confidence: 99%
“…However, with a smaller steric effect, the alkyl-pyridine ligands will bind four copper atoms, generating a tetracopper complex 39 [77]. Similarly, three dicopper compounds 40-42 based on 1-azaallyl, aryl-phosphanimine, and aryl-imine ligands were synthesized from the corresponding lithiated starting materials and copper salts by Lappert [78], Stalke [79], and Schmidt [82], respectively. The Cu-C bonds of 37-40 are in the range of 1.93-1.95 Å, which suggests a mostly 2c-2e Cu-C bond, while the Cu-C As shown in Scheme 11, the C,N-chelated dicopper compounds 37,38 and 40-42 documented in the literature are generally macrocyclic neutral species since the two negative ligand charges are exactly balanced with two Cu(I) atoms [76][77][78][79][80][81][82].…”
Section: Binuclear Macrocyclic Copper Complexesmentioning
confidence: 99%
“…Utilizingt he potential of this non-conventionald irecting group, Schmidt and co-workersh ave published several studies [36][37][38][39] on the directed ortho-lithiationo fawide variety of 3,4methylenedioxyphenyl imines.S elective lithiation in all cases is achieved using commercial nBuLi in pentane at À78 8Co r08C (Scheme5). These anionic units are used as ancillary ligands, via metathesis reactions, to afford aw ide variety of metal complexes including Mg, [38] Zn, [38,40] Al, [38] Cu I , [38] Ti, [37,39] Zr, [39] Nb, [36] Ta , [36] and Sn IV . [38] Al arge number of these metal complexes have been successfully characterisedi nt he solid state highlighting the importance of the imine nitrogen atom providing extra stabilityt hrough chelation to the metal centre.…”
Section: Directing Groupsmentioning
confidence: 99%
“…Utilizing the potential of this non‐conventional directing group, Schmidt and co‐workers have published several studies [36–39] on the directed ortho ‐lithiation of a wide variety of 3,4‐methylenedioxyphenyl imines. Selective lithiation in all cases is achieved using commercial n BuLi in pentane at −78 °C or 0 °C (Scheme 5).…”
Section: Metallationmentioning
confidence: 99%
“…However, the literature search showed that the applying of N, C-or N,C,N-chelating ligands in the chemistry of Zn or Cd provided homoleptic intramolecularly N-stabilized organozinc, or cadmium compounds of the general formula MR 2 (M = Zn, Cd; R = {2-(CH 2 NEt 2 )C 6 H 4 } -, {2,6-(CH 2 NMe 2 ) 2 C 6 H 3 } -, {2,6-(CH 2 NEt 2 ) 2 C 6 H 3 } -, {2, regardless of the stoichiometry used [10]. Finally, Liu and co-workers reported on the synthesis of {2,6-[CH=N(2',6'-i Pr 2 C 6 H 3 )] 2 C 6 H 3 )ZnEt by the use of N,C,N-chelating ligand [11].…”
Section: Introductionmentioning
confidence: 99%